Turkish version of the SHARE-Frailty Instrument for primary care: reliability and validity in the nursing home setting - Romero-Ortuno, Roman (My University, 2023)
In Turkey, physical frailty instruments have not been studied in the nursing home setting. We determined the reliability and validity of a Turkish version of the SHARE-Frailty Instrument for primary care (SHARE-FI) in Turkish nursing home residents. Cronbach’s alpha reliability analysis was performed to determine internal consistency. Factor analysis was conducted to explore construct validity. Concurrent validity was assessed by correlation with the Care Dependency Scale (CDS). One hundred and fifty-one residents were included (mean age 73 years, 41% women). Fifty (33.1%) were identified as non-frail, 49 (32.5%) as pre-frail, and 52 (34.4%) as frail by SHARE- FI. The overall Cronbach’s alpha coefficient was 0.81. Factor analysis identified two components accounting for 69% of the variance, with the first and most important component being handgrip strength. SHARE-FI groups were significantly correlated with CDS scores (p<0.05). The Turkish version of SHARE-FI had good reliability and validity in a nursing home setting.
PUBLISHED
Keywords: Care dependency; Frailty; Geriatric care; Nursing home; Validation studies; Ageing; Inclusive Society; Age-related disability; Health; Third age/ageing